PECULIARITIES OF DESIGN OF MODERN COWORKING SPACES DEPENDING ON THEIR FUNCTIONAL PURPOSE - Шмельова, О. Є.; Сафронова, О. О.; Булгакова, Т. В.; Синицька, М. О. (Art and Design, 2020)
The purpose of the research is to determine features of interior design of modern coworkings. The following methods were used for the purposes of research: method of systematic analysis of specialized resources and scientific publications on the research topic; method of comparative analysis within the typology and for each type separately; generalization and systematization of information obtained in the process of research. Experience and tendencies of designing coworkings as a new formation of multifunctional public objects in the information society that meet modern requirements of organizing an informal workspace have been studied in order to provide for the new forms of activity and recreation; peculiarities of the design of coworking premises have been analyzed depending on their purpose and processes that are to take place in them; classification of the coworking spaces according to different functional characteristics has been elaborated; links between the typological features of the coworking spaces and their design solutions were established. The principal components of the coworking space (basic and additional) are identified; classification of coworking spaces by typological features are extended and refined; relation between the said features and formation of design solutions of the most common coworking space types are established and substantiated. The following peculiarities of interior design of coworkings will be useful for the modern practice of designing different types of researched spaces, and will help to solve such design problems as planning structure, object-space filling and stylistic design.